2021
DOI: 10.3390/nu13041151
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Use of Pasteurized Donor Milk for Healthy Newborns: Experience from the First Human Milk Bank in Vietnam

Abstract: Background: Pasteurized donor milk (PDM) is typically prescribed to preterm or low birthweight newborns when their mother’s own milk is unavailable. In surplus, PDM is prescribed to meet the nutritional needs of healthy newborns in the first few days of life. However, its overuse can undermine efforts to promote and support breastfeeding, waste resources, and reduce the availability of PDM for at-risk newborns. We conducted this study to examine factors associated with the prescription and prolonged use (>4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(50 reference statements)
0
3
1
Order By: Relevance
“…Our findings indicated that the willingness to use DHM decreased with monthly household income in the previous year. In contrast, a study done in Vietnam showed that families with a higher income were more likely to use pasteurized DHM to feed their healthy newborns [45]. The difference might be explained by the fact that the mothers in our study were unfamiliar with human milk banks and were unsure of the safety of DHM, whereas in good economic circumstances, they would rather afford expensive but relatively safe infant food, such as formula, to feed their infants.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Our findings indicated that the willingness to use DHM decreased with monthly household income in the previous year. In contrast, a study done in Vietnam showed that families with a higher income were more likely to use pasteurized DHM to feed their healthy newborns [45]. The difference might be explained by the fact that the mothers in our study were unfamiliar with human milk banks and were unsure of the safety of DHM, whereas in good economic circumstances, they would rather afford expensive but relatively safe infant food, such as formula, to feed their infants.…”
Section: Discussioncontrasting
confidence: 65%
“…In our study, parity was not significantly associated with women's willingness to donate human milk. However, the results of other studies [29,45] indicated that multiparous mothers had a positive attitude toward human milk donation. A possible explanation for the difference might be that new mothers in our study, although inexperienced, learned about the benefits of human milk through breastfeeding promotion programs provided by the government and hospitals, made their own efforts to breastfeed, and supported other mothers in feeding their infants with human milk.…”
Section: Discussionmentioning
confidence: 89%
“…The DHM in our HMB was only supplied to the neonates in our NICU and was not continued after discharge, and it was provided free of cost. This model is different from that described in previous reports from Thailand and the UK,which provide DHM for non-hospitalized infants [24,25]. During the 8-year period, 9,207 newborns received DHM, most of whom were premature infants (80.1%), and the newborns had severe infection, feeding intolerance, and necrotizing enterocolitis.…”
Section: Recipientsmentioning
confidence: 73%
“…Breastfeeding is an unequalled way of providing ideal food for the healthy growth and development of infants, and it plays a crucial role in ensuring their survival (World Health Organization [WHO], 2023). However, there are situations in which newborns cannot be breastfed for reasons that include illness, maternal death, lack of social support, an underdeveloped sucking reflex, low birth weight, premature birth, low lactation capacity, or separation of the mother and infant (Tran et al, 2021; Zhang et al, 2022). In such cases, the WHO (2022) recommends alternative feeding methods such as using donor milk, formula, or artificial feeding when breastfeeding is not possible or contraindicated.…”
Section: Introductionmentioning
confidence: 99%